The Relation of Carotid Calcium Volume with Carotid Artery Stenosis in Symptomatic Patients - Marquering, H.A. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: Recent research showed a strong correlation of calcium volume scores with degree of stenosis, suggesting that calcium volume could be used in the diagnosis of carotid artery stenosis. We investigated the accuracy of the use of calcium volume scores to diagnose carotid artery stenosis in our target population of recently symptomatic patients. MATERIALS AND METHODS: Ninety symptomatic patients suspected of having carotid artery stenosis underwent CTA, resulting in images of 159 evaluable arteries. The correlation between calcium volume and degree of stenosis was calculated by using the Pearson correlation coefficient. With thresholds of 0.03 and 0.09 mL, we assessed the diagnostic performance of a calcium volume−based evaluation of stenosis for a previously reported stenosis cutoff of 40% and for the clinically important cutoffs of 50% and 70%. RESULTS: In our patients series, the calcium volume score was not related to the stenosis degree on the symptomatic side (R = 0.04, P = .7) and was weakly related on the asymptomatic side (R = 0.29, P = .005). The diagnostic accuracy of the calcium volume score to estimate 40% stenosis was relatively low: a sensitivity of 47% or 64% and a specificity of 52% or 82%, for the 0.09 and 0.03 mL thresholds, respectively. The diagnostic accuracy decreased with increasing degree of stenosis. CONCLUSIONS: We could not confirm the previously reported strong correlation of calcium volume with stenosis degree in our population of patients with recent neurologic symptoms. We conclude that in this particular domain, calcium volume cannot be used to estimate the degree of stenosis.